Lipid lowering with inclisiran: a real-world single-centre experience. Issue 2 (13th December 2022) - Padam, Pritpal; Barton, Lucy; Wilson, Stewart; David, Alessia; Walji, Shahenaz; de Lorenzo, Ferruccio; Ray, Kausik K; Jones, Ben; Cegla, Jaimini
Abstract : Objective: The reduction in circulating low-density lipoprotein cholesterol (LDL-c) is the primary aim of lipid-lowering therapies as a method of atherosclerotic cardiovascular disease risk reduction. Inclisiran is a new and potent lipid-lowering drug that is shown to be effective in reducing LDL-c in randomised controlled trials, however, real-world data of its use are not yet known. We sought to analyse the early effects of this drug in a tertiary centre lipid and cardiovascular risk clinic. Methods: We performed a retrospective analysis of the first 80 patients who received a single dose of inclisiran at our lipid clinic between 1 December 2021 and 1 September 2022. Data were collected using electronic healthcare records. Baseline blood tests were taken prior to start of treatment and were repeated at 2 months follow-up. Data on adverse events were also recorded. Results: At 2 months after treatment initiation, mean baseline LDL-c fell from 3.5±1.1 mmol/L by 48.6% to 1.8±1.0 mmol/L and total cholesterol from 5.7±1.3 mmol/L by 33.3% to 3.8±1.1 mmol/L (both p<0.0001). Mean high-density lipoprotein-c rose by 7.7% to 1.4±0.4 mmol/L (p=0.02) and median triglycerides fell by 31.3% to 1.1 mmol/L (IQR 0.9–2) (p=0.001). Adverse events (injection site reaction, fatigue and headache) were recorded in three patients and all had self-resolved by time of follow-up. Conclusion: Inclisiran use in line with National Institute for Health and Care Excellence guidelines led to significant lowering of LDL-c at 2 months, with efficacy similar to that reported in trials with good tolerability.